Selective Water-Soluble Gelatinase Inhibitor Prodrugs - Gooyit, Major (2011)
SB-3CT (1), a selective and potent thiirane-based gelatinase inhibitor, is effective in animal models of cancer metastasis and stroke; however, it is limited by poor aqueous solubility and extensive metabolism. We addressed these issues by blocking the primary site of metabolism and capitalizing on a prodrug strategy to achieve >5000-fold increased solubility. The amide prodrugs were quantitatively hydrolyzed in human blood to a potent gelatinase inhibitor, ND-322 (3). The arginyl amide prodrug (ND-478, 5d) was metabolically stable in mouse, rat, and human liver microsomes. Both 5d and 3 were non-mutagenic in the Ames II mutagenicity assay. The prodrug 5d showed moderate clearance of 0.0582 L/min/kg, remained mostly in the extracellular fluid compartment (Vd = 0.0978 L/kg), and had a terminal half-life of >4 h. The prodrug 5d had superior pharmacokinetic properties than 3, making the thiirane class of selective gelatinase inhibitors suitable for intravenous administration in treatment of acute gelatinase-dependent diseases.